When Seeking the Best Brings Out the Worst in Consumers: Understanding the Relationship between a Maximizing Mindset and Immoral Behavior. Issue 2 (15th December 2017) - Goldsmith, Kelly; Roux, Caroline; Ma, Jingjing
Abstract : Consumers often adopt a goal to choose "the best" option: be it the best value for their money, the product with the highest quality, or the product that offers the best match to their idiosyncratic preferences. Prior work has characterized this orientation as a "maximizing mindset, " and has demonstrated that the adoption of a maximizing mindset can lead to both positive and negative consequences for the self. However, to date, little is known about if a maximizing mindset might have consequences beyond the self (i.e., for others and/or society). The current article addresses this gap by demonstrating that consumers who adopt a maximizing mindset (vs. a neutral mindset) are subsequently more likely to engage in immoral behaviors. Further, we demonstrate that this effect occurs because a maximizing mindset activates cognitions related to scarcity. In doing so, the current research offers a more nuanced understanding of the psychological and behavioral consequences of a maximizing mindset and identifies a maximizing mindset as an antecedent to cognitions related to scarcity and immoral behaviors. Abstract : This article is part of the issue "Marketplace Morality"